China’s Treatment of Crimes against the Environment: Using Criminal Sanctions to Fight Environmental Degradation in the PRC - Chun-xi, Yang; Head, John W.; Sheng-Rong, Liu (Columbia Journal of Asian Law, 1994)
Change is coming rapidly to the People’s Republic of China (the “PRC” or “China”), especially in three related areas – degradation of its physical environment, transformation of its economic system and modernization of its legal system. This Article examines a development that lies at the intersection of these three areas of change: the use of criminal law in the fight against environmental degradation in the PRC.